2021
DOI: 10.1186/s12916-021-02183-2
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle correlates of eight breast cancer-related metabolites: a cross-sectional study within the EPIC cohort

Abstract: Background Metabolomics is a promising molecular tool for identifying novel etiological pathways leading to cancer. In an earlier prospective study among pre- and postmenopausal women not using exogenous hormones, we observed a higher risk of breast cancer associated with higher blood concentrations of one metabolite (acetylcarnitine) and a lower risk associated with higher blood concentrations of seven others (arginine, asparagine, phosphatidylcholines (PCs) aa C36:3, ae C34:2, ae C36:2, ae C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Comparing these results to previous studies is complex; this analysis primarily investigated metabolite patterns rather than individual metabolites. Broadly in line with our results, however, positive associations of alcohol intake with some of the metabolites loading on metabolite pattern 1 (phosphatidylcholines and hydroxysphingomyelins) have previously been reported in other analyses [24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Comparing these results to previous studies is complex; this analysis primarily investigated metabolite patterns rather than individual metabolites. Broadly in line with our results, however, positive associations of alcohol intake with some of the metabolites loading on metabolite pattern 1 (phosphatidylcholines and hydroxysphingomyelins) have previously been reported in other analyses [24][25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…The current analyses have identified dietary (fish and alcohol) and anthropometric (BMI) correlates of three metabolite patterns that were previously found to be inversely associated with more aggressive prostate cancer subtypes [1]. The implications of these associations are not yet clear; fish [33][34][35][36][37][38][39][40][41] and alcohol intakes [42][43][44][45][46][47][48][49][50][51] are not established risk factors for prostate cancer, while any associations of BMI with prostate cancer risk, of which positive associations with advanced disease and death have previously been reported [52], might be due to differences in the timing of detection of prostate cancer in men with obesity compared to men with a normal BMI [27,[53][54][55][56][57]. Furthermore, research is ongoing to determine whether the metabolite pattern-prostate cancer associations previously reported are likely to be causal.…”
Section: Discussionmentioning
confidence: 99%
“…A first approach is to build on the results of studies where novel metabolites were found to be associated with breast cancer risk, as in EPIC. 27 Concentrations of PCs ae C34:2, C36:2, C36:3, and C38:2 were found to be inversely associated with adiposity and positively associated with total and saturated fat intakes. PC ae C36:2 was also inversely associated with alcohol consumption and positively associated with a healthy lifestyle.…”
Section: Linking Metabolites Breast Cancer and Lifestylementioning
confidence: 91%
“…The authors 54 found that reduced adiponectin and increased inflammatory biomarkers, C-peptide, and estrogens mediated approximately 70% of increased odds of endometrial cancer in women with obesity vs normal weight. 54 In another study, His and colleagues 55 evaluated the link between serum metabolite concentrations, lifestyle, adiposity, and breast cancer. Blood concentrations of acetylcarnitine, a metabolite, and breast cancer risk have been reported as well as lower risk associated with higher blood concentrations of seven other metabolites.…”
Section: Molecular Pathways and The Tumor Microenvironmentmentioning
confidence: 99%